Flexural properties evaluation of carbon-fiber fabric reinforced poplar/eucalyptus composite plywood formwork. (15th September 2019) - Liu, Yuansong; Guan, Mingjie; Chen, Xianwen; Zhang, Yuan; Zhou, Mingming
Highlights: High value-added poplar/eucalyptus/carbon fiber composite formwork was developed. The impact and bending of the four reinforced structures were evaluated. The flexural properties of the composite formwork were significantly improved. The failure mode and mechanism of the composite were analyzed and evaluated. Abstract: To improve the product quality of traditional wooden building formwork, utilize the resources of wood and evaluate the failure mode of the formwork. Carbon-fiber fabric (CF fabric) reinforced poplar/eucalyptus composite plywood were prepared by using fast-growing poplar (P) and eucalyptus (E) veneer as base materials and CF fabric as reinforcement material, four substrate composite structures (P/P, E/E, P/E, E/P) and four reinforcement positions (control/A, surface/B, core/C and surface-core/D) were considered in this study, the flexural properties and failure modes of plywood were tested and evaluated. Experimental results showed that the flexural performance of plywood as poplar/eucalyptus composite structure was better than pure poplar and eucalyptus. The increase in the longitudinal modulus of elasticity and modulus of rupture of the plywood was particularly understandable and the failure mode was shear delamination failure after the surface strengthened, besides, the core layer reinforced transverse plywood was greater obvious than the longitudinal plywood for the improvement in impact toughness. However, the plywood strengthened by the surface and core simultaneously had the best performance, and the structure which satisfies the strength requirements of building formwork are D-P/E and D-E/P. Experimental findings are accompanied with theoretical model.